2023
DOI: 10.1038/s41598-023-31412-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the use of large language model in identifying top research questions in gastroenterology

Abstract: The field of gastroenterology (GI) is constantly evolving. It is essential to pinpoint the most pressing and important research questions. To evaluate the potential of chatGPT for identifying research priorities in GI and provide a starting point for further investigation. We queried chatGPT on four key topics in GI: inflammatory bowel disease, microbiome, Artificial Intelligence in GI, and advanced endoscopy in GI. A panel of experienced gastroenterologists separately reviewed and rated the generated research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
42
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 13 publications
2
42
0
1
Order By: Relevance
“…The version column in Table 2 shows the version of ChatGPT used for evaluation. [63] found that newer versions of ChatGPT tend to have better performance on the same questions. In contrast to using ChatGPT directly for writing, which is expressly banned by many scientific journals, exploring new research ideas/topics with the assistance of ChatGPT faces less ethical issues.…”
Section: Reviews Of Level 3 Papersmentioning
confidence: 91%
See 4 more Smart Citations
“…The version column in Table 2 shows the version of ChatGPT used for evaluation. [63] found that newer versions of ChatGPT tend to have better performance on the same questions. In contrast to using ChatGPT directly for writing, which is expressly banned by many scientific journals, exploring new research ideas/topics with the assistance of ChatGPT faces less ethical issues.…”
Section: Reviews Of Level 3 Papersmentioning
confidence: 91%
“…A few studies evaluate the use of ChatGPT in medical research, particularly in scientific writing [67] and generating research questions [63] and systematic review topics [38]. In [67], the authors use ChatGPT to generate full abstracts, providing only the title and result sections of the abstracts from 50 real scientific publications.…”
Section: Reviews Of Level 3 Papersmentioning
confidence: 99%
See 3 more Smart Citations